A Degree Achieving Phonemic Awareness Skills in Arabic Language Curricula for the First Three Grades in the State of Qatar - Morsi, Iman Mohamed; Hassanein , Elsayed Elshabrawi Ahmad (Dirasat: Educational Sciences, 2023)
Objectives: The current study aims to investigate the degree of achievement of phonemic awareness skills in the Arabic language curriculum for the first three grades in the State of Qatar. The study seeks to ensure that this content is presented sufficiently, appropriately, and organized in terms of quantity and quality. Methods: To achieve the study’s goal, the descriptive analytical method was employed. A content analysis form was developed to measure phonemic awareness skills, which were distributed across the curricula of the three grades. Results: The analysis revealed that certain phonemic awareness skills were well achieved, while others exhibited some drawbacks in terms of their relative weight in the curriculum, their presentation, or both. Conclusions: Based on the findings of this study, it is recommended to reconsider the distribution of phonemic awareness skills within the specific curricula. Furthermore, a comparative analysis of the curriculum against other effective curricula that provide phonemic awareness skills is suggested to leverage their experience.